ESP Learners Pronounce in New Trend (You Tube) Application: Instructor's Perception and Practice - Faturrachman, Yani; Ulva, Siti Maria (English Education:Journal of English Teaching and Research, 2021)
The aim of teaching English for Specific Purposes (ESP) is not to imitate the native speakers or to develop the British or American accents. English communication influences the first language or mother tongue for ESP learners. Meanwhile, According to Evan (1997), ESP has some characteristics, such as: firstly, ESP may be related or designed for specific disciplines, secondly, ESP may be used in specific teaching situations and has different methodology from that of General English (GE); thirdly, ESP is likely to be designed for adult learners, either at a tertiary level education or in a professional work situation; fourthly, most ESP courses take on some basic knowledge of the language systems. This research used descriptive qualitative research as a design to gather or collect the data because of the current phenomenon to explain the error of pronunciation and the causes of error in pronouncing words. This paper will be done by researchers at Management Class who learn the ESP program in Kaltara University. This research also used observation field notes and interview guide as the instruments. Hence, the researchers found that there were fifteen pronunciation errors who were presented by ESP learners’ mother tongue in learning speaking through YouTube Application. Besides, there were four materials in You Tube Application that pronounced by ESP Learners such as: Promotion, Bargaining, Complaining, and Response.